How Human Resources Management Practice And Change Management Contribute To The Small Medium Enterprises Performance - Bagus Kusuma; Andhika Kautsar (Fakultas Ekonomi Universitas Warmadewa, 2020)
SMEs (small and medium enterprises) food & beverage is one type of business that plays a role in improving the economy in Indonesia. This research has a goal to explore for some owner/manager of SMEs in managing change, recognizing the importance of the people within the company, and knowing the ability of the owner/manager of SMEs in adapting and developing new learning and skill. The observation is conducted in Bandung with an in-depth interview and questionnaire method to 30 respondents involving 10 SME owners/managers in in-depth interview. The analysis of the mixed method finds that the solution of the existing issue of change management needs to be done to help the occurrence of change management. Therefore, the system in the company concerned with human resources can be improved so that talent management will be more efficient and targeted.